INTERNAL CONFLICTS OF RELIGIOUS ADOLESCENTS WHO VIOLATE RELIGIOUS NORMS: A QUALITATIVE PHENOMENOLOGICAL STUDY - Junaidi Junaidi; Riyandha Dwi Saputra; Agus Machfud Fauzi (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This research aims to understand the internal conflicts experienced by religious adolescents who violate religious norms. Despite having a high level of religion, such as regularly carrying out worship and participating in religious activities, some adolescents are still involved in deviant behavior, such as drinking, promiscuity, and violence. Using a qualitative phenomenological approach, the study explores the subjective experiences and inner dynamics of adolescents who face the contradiction between their religious beliefs and behaviors. The data was obtained through in-depth interviews with ten teenagers who were considered religious but had been involved in violations of religious norms. The results showed that these adolescents experienced significant inner conflict, which arose from the imbalance between the religious values they professed and the social and emotional pressures they faced. Factors such as social influence, self-identity search, and emotional urges are the main triggers of deviant behavior. These findings reveal the importance of emotional support, a conducive environment, and holistic religious guidance in helping adolescents cope with these internal conflicts.